Reasons for misdiagnosis of polymyositis in patients with dysferlinopathy: a clinical case - S. N. Bardakov; A. М. Emelin; S. S. Nikitin; A. N. Khelkovskaya-Sergeeva; I. S. Limaev; A. F. Murtazina; V. A. Tsargush; M. V. Gusev; Ya. V. Safronova; V. S. Kaimonov; A. A. Isaev; R. V. Deev (Нервно-мышечные болезни, 2022)
Differential diagnosis of inflammatory myopathies with hereditary muscular dystrophies accompanied by a secondary inflammatory process is a time‑consuming clinical and pathomorphological task. In particular, false diagnosis of polymyositis in patients with dysferlinopathy reaches 25 % of cases.A 40‑year‑old female patient with a limb‑girdle phenotype of dysferlinopathy, initially diagnosed as polymyositis, is presented. The reasons that led to the erroneous diagnosis were: sporadic case; subacute onset; proximal muscle weakness; myalgia, which stopped on the glucocorticosteroid therapy; high levels of creatine phosphokinase (up to 17 times); the presence of lymphocytic‑macrophage infiltrate in the muscle biopsy and the absence of magnetic resonance imaging data in primary examination of the patient.The refractoriness of clinical and laboratory signs to complex immunosuppressive therapy was the reason for revising the muscle biopsy with typing of the inflammatory infiltrate. The predominantly unexpressed perivascular infiltrate was characterized by the predominance of macrophages and, to a lesser extent, CD4+, which indicated the secondary nature of the inflammation in the muscle observed in some hereditary muscular dystrophies. When conducting an immunohistochemical reaction, the absence of the dysferlin protein in the sarcoplasmic membrane was revealed.Whole‑exome sequencing (NGS) revealed a mutation in exon 39 of the DYSF gene (p.Gln1428Ter) in the heterozygous state, which leads to the appearance of a stop codon and premature termination of protein translation. MLPA method registered 3 copies of exons 18, 19, 20, 22, 24 of the DYSF gene.Thus, this clinical example reflects the main methodological errors and possible effects of immunosuppressive therapy in patients with dysferlinopathy.